Energy and exergy efficiency analysis for biogas De-CO2 with tetra-n-butylammonium bromide hydrates. (15th February 2023) - Huang, Hong; Fan, Shuanshi; Wang, Yanhong; Lang, Xuemei; Li, Gang
Abstract: The two-stage hydrate-based biogas De-CO2 process in the presence of TBAB was simulated by ASPEN plus software. Energy consumption, sensitivity analysis of key process parameters and exergy of the whole process were calculated and analyzed. The results show that reduce the hydrate formation pressure from 4 MPa to 1 MPa, the energy consumption of the whole process is reduced by 18.1%. When the gas-liquid ratio is reduced from 100 to 40, the stirring energy consumption increases by 134%, and the whole process energy consumption increases by 33.6%. The decrease of CH4 recovery rate has a significant and negative impact on energy consumption efficiency. The exergy loss of hydrate formation and dissociation unit is more than 73%. After optimizing with utilization of process energy, the power generation of product gas is 6.8 kWh/Nm 3, the total energy consumption was reduced by 22.3%, and the energy cost was lowered to 0.451 kWh/kg CO2, which has advantages compared with other conventional carbon capture processes. Graphical abstract: Image 1 Highlights: The energy and exergy of HBBDC technology was analyzed for the first time. The key points of reducing energy consumption and improving exergy efficiency of HBBDC technology are determined. HBBDC technology has obvious advantages compared with the traditional De-CO2 technologies.